Pengaruh Kualitas Pelayanan dan Biaya Penitipan (Ujrah) Terhadap Kepuasan Nasabah Gadai Emas: Studi Kasus Pada Pegadaian Syariah UPS Manggis Bukittinggi - Mariatul Qoftia; Novera Martilova (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
The aim of this research is to determine "the influence of deposit fees (ujrah) and service quality on gold pawn customer satisfaction at the Bukittinggi Syariah Pegadaian". This investigation uses quantitative methodology, specifically an associative approach. The sample size is determined by the size of the population; because the number of individuals in the population was less than 100, the entire sample was used. Primary data was collected from respondents through distributing questionnaires. Meanwhile, multiple linear regression, classical assumption testing, and hypothesis testing were used to analyze the data. The results of hypothesis testing show that gold pawn customer satisfaction at sharia pawnshops is influenced simultaneously by the variables of service quality and deposit fees (ujrah). This is supported by a significant value of 0.025 <0.05. With a value of 0.042 <0.05, the service quality variable has a partially significant effect on consumer satisfaction with gold pawning at sharia pawnshops. With a significance level of 0.020 <0.05, the deposit cost variable (ujrah) has a significant effect on consumer satisfaction with gold pawning at sharia pawnshops. Based on the findings of this research, it can be concluded that service quality and deposit fees (ujrah) influence consumer satisfaction with gold pawning at sharia pawnshops by 10.9%. The remaining 89.1% is caused by foreign variables.